Estrategias de comunicación digitales utilizadas en la página de Facebook de rescate animal Ecuador - Landívar Córdova, Gabriela Marita (2023)
Within the next work, Digital communication strategies used in the Facebook page of Rescate Animal Ecuador, there is the problem that Ecuador is a country with high rates of animal abuse, so there are movements such as animal rescue Ecuador, which on its Facebook page promotes the care and calls for the protection of animals, for this they use communication strategies oriented to digital channels. There is the benefit of giving an external view to their strategic communication model and identify if it needs changes, in addition to highlighting successes and useful concepts for other animal rescue foundations. This following the objective of analyzing the digital communication strategies used in the Facebook page of Rescate Animal Ecuador through which it was possible to explore the concepts of animal foundation, digital communication strategies, the needs of communication strategies, animal abuse, social networks, advertising and campaigns. Measured through the inductive-deductive, quantitative and qualitative methodology, with techniques of the interview to a marketing expert and the selected survey to 101 participants. Where it was found that 65% do know any animal rescue foundation, while 35% do not know any animal rescue foundation, while 35% do not know any animal rescue foundation. rescue foundation, while 35% do not know any animal rescue foundation. That communication strategies really require factors such as the target audience, the objectives of the organization the target audience, the objectives of the organization, being able to apply strategies such as awareness campaigns and strategies such as awareness campaigns and online advertising. Concluding that animal rights violations exist in the country, and that these are exposed in Rescate Animal networks, and use effective digital communication strategies through the effective digital communication strategies through the sharing of emotive information that calls for citizen intervention, recommending greater interaction with users in the networks.